Endoplasmic Reticulum Stress Induces the Expression of Fetuin-A to Develop Insulin Resistance - Ou, Horng-Yih; Wu, Hung-Tsung; Hung, Hao-Chang; Yang, Yi-Ching; Wu, Jin-Shang; Chang, Chih-Jen (Endocrinology (Philadelphia), 2012)
Fetuin-A is a biomarker reported to be important in many metabolic disorders, including obesity, diabetes, and hepatic steatosis. Although it is well known that fetuin-A is increased in diabetes and nonalcoholic fatty liver disease (NAFLD), the levels of fetuin-A in diabetic patients with NAFLD are unknown. Furthermore, the regulation of fetuin-A expression is still obscure. In this study, a total of 180 age- and sex-matched subjects with normal glucose tolerance, NAFLD, newly diagnosed diabetes (NDD), and NDD with NAFLD were recruited. We found that the levels of fetuin-A were significantly increased in NDD with NAFLD as compared with NDD or NAFLD subjects. We further used HepG2 cells to investigate the regulation of fetuin-A. Treatment with endoplasmic reticulum (ER) stress activator, thapsigargin, increased the expression of fetuin-A mRNA and protein in a time- and dose-dependent manner. Pretreatment with ER stress inhibitor, 4-phenylbutyrate, reversed high glucose or palmitate-induced fetuin-A expression. Moreover, treatment with 4-phenylbutyrate in both streptozotocin-induced and high-fat diet-induced diabetic mice not only decreased hepatic fetuin-A levels but also improved hyperglycemia. Taken together, we found that fetuin-A levels were increased in diabetes patients with NAFLD. Moreover, ER stress induced by high glucose and palmitate increased the expression of fetuin-A and further contributed to the development of insulin resistance.